2021
DOI: 10.3390/cancers13133144
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Incidence and Outcome of Bone Metastases in Clinical Trials Enrolling Patients with Epidermal Growth Factor Receptor Mutated Lung Adenocarcinoma—A Systematic Review

Abstract: Bone metastases, occurring in 30–60% of patients with non-small cell lung cancer (NSCLC), are associated with decreased survival, cancer-induced bone pain, and skeletal-related events (SREs). Those with an activating epidermal growth factor mutation (EGFR+) seem to be more prone to develop bone metastases. To gain more insight into bone metastases-related outcomes in EGFR+ NSCLC, we performed a systematic review on Pubmed (2006–2021). Main inclusion criteria: prospective, phase II/III trials evaluating EGFR-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Baseline and cumulative incidence of bone metastases and SREs is high in patients with EGFR+ metastatic NSCLC treated with first- and second-generation EGFR TKIs, and therefore, better treatment options are necessary. 11 We found that most patients (45%) already had bone metastases at first diagnosis of metastatic NSCLC, and this percentage increased to 51% at initiation of osimertinib if patients were treated with osimertinib in second line and beyond. At diagnosis of metastatic EGFR+ NSCLC, 15% of patients with bone metastases were diagnosed with having an SRE, and the cumulative incidence increased to 39%.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Baseline and cumulative incidence of bone metastases and SREs is high in patients with EGFR+ metastatic NSCLC treated with first- and second-generation EGFR TKIs, and therefore, better treatment options are necessary. 11 We found that most patients (45%) already had bone metastases at first diagnosis of metastatic NSCLC, and this percentage increased to 51% at initiation of osimertinib if patients were treated with osimertinib in second line and beyond. At diagnosis of metastatic EGFR+ NSCLC, 15% of patients with bone metastases were diagnosed with having an SRE, and the cumulative incidence increased to 39%.…”
Section: Discussionmentioning
confidence: 74%
“…In other series (including a systematic review) evaluating EGFR TKI trials (N = 1196) and several retrospective series evaluating patients (N = 126–1081) treated with EGFR TKI, the percentage of patients with bone metastases at diagnosis of metastatic NSCLC was similar to our study ( Supplementary Table 1 ). 11 , 23 Nevertheless, data about bone progression and development of SREs during EGFR TKI treatment are scarce. 11 The percentage of patients who develop bone progression during osimertinib in our series is comparable with that of a smaller series (N = 126) evaluating outcomes on first-line osimertinib (10% versus 12%) and with trials evaluating first- and second-generation EGFR TKIs (11% versus 3%–26%) ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized clinical trials have shown that front-line treatment with first-, second-, and third-generation EGFR -tyrosine kinase inhibitors (TKIs) greatly improved the survival outcomes of advanced EGFR -mutated NSCLC patients [ 5 ]. However, investigations about the prognosis of EGFR -mutated NSCLC patients with bone metastasis are limited [ 7 ].…”
Section: Introductionmentioning
confidence: 99%